Phenological variation within several Algerian populations of sulla (Hedysarum coronarium L., Fabaceae) - Issolah R.; Yahiaoui S. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
As part of the characterization and the valorization of plant genetic resources of fodder and pastoral interest in Algeria, twenty natural populations of Hedysarum coronarium L. were subject to a phenological study for two consecutive years. Eighteen characteristics linked to the vegetative development, bloom and fruiting heads were studied. The ecological factors (rainfall, altitude) of the original environment of the populations were taken into account during this study. Certain variability was noticed. The results indicated that the plant is characterized by an interesting vegetative development, particularly during the second year of growth. Relations seem to exist between some phenological characteristics and factors of the populations' original environment. Hedysarum coronarium L. should be developed, particularly in isolated and disadvantaged areas, to which it could adapt.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)